A Multicenter, Randomized, Parallel-Group Trial Assessing Compliance, Tolerability, Safety, and Efficacy to Treatment with Grass Allergy Tablets in 261 Patients with Grass Pollen Rhinoconjunctivitis. (9th November 2011) - Alesina, Roberta; Milani, Massimo; Pecora, Silvia
Abstract : Background . Allergen-specific sublingual immunotherapy (SLIT) is considered a causal treatment of respiratory allergies. Compliance to the SLIT is an important aspect for a positive clinical outcome. Study Aim . To evaluate if compliance with grass Allergy Immunotherapy Tablet (AIT) can be increased by providing an electronic compliance device (CED) (Memozax; a tablet-container with a programmable daily acoustic alarm). Patients and Methods . 261 patients with grass allergy were enrolled and randomized (1 : 1) to 1-year treatment with AIT (Grazax) using a CED (group A; n = 122 ) or without (Group B, n = 139 ). Compliance was measured through tablet count at each visit. Results . The 12-month compliance, mean (SD), in group A was 83% (21) and 83% (24) in group B. A total of 81% of patients reported a significant clinical improvement of symptoms after treatment in comparison with the previous year. No severe adverse reactions were observed in the study. Conclusion . Compliance to the treatment with AIT administered for 12 consecutive months is in general good. The use of CED is not associated with a greater compliance. AIT treatment was associated with a significant clinical improvement in >80% of patients with a good tolerability and safety profile.